A funç\~ao do estado no setor de energia nos países da OCDE: Equilibrando a segurança energética, a eficiência e a sustentabilidade - Maria Bernadete G. P. Sarmiento Gutierrez (Instituto de Pesquisa Econômica Aplicada (IPEA), 2021)
– The reform process in the energy sector in Organisation for Economic Co-operation and Development (OECD) and in emerging countries started in the 1990s, aimed at reducing the role of the state as a shareholder, but not in its function as coordinator, regulator and planner. Also, it should be stressed that the transition to a low carbon economy in the 21th century has enlarged the state's agenda, in particular towards reaching the Sustainable Development Goals (SDG) 7: Acessible and clean energy. The state remains an important actor in the energy sector, in the search for energy security, efficiency and sustainability. As a first step, this study attempts at defining the rationality, the participation and the diversity associated with the state in the energy sector, at the same time suggesting the beneficial effects of the state-private sector partnership. In a second instance, the PMR OECD database is analysed for the energy sector, in the light of the reforms and governance structures for selected countries, at the same time establishing a parallel with Brazil's performance in terms of state ownership, regulatory aspects and liberalization degree.
Keywords: Q48; 330; energy sector; reforms; efficiency; sustainability; security